Chemistry the central science - Brown, Theodore L. (Theodore Lawrence) 1928-; LeMay, H. Eugene (Harold Eugene) 1940-; Bursten, Bruce Edward; Murphy, Catherine J.; Woodward, Patrick M.; Stoltzfus, Matthew W.; Lufaso, Michael W. (Pearson Education Limited, 2018)
For courses in two-semester general chemistry. Accurate, data-driven authorship with expanded interactivity leads to greater student engagement Unrivaled problem sets, notable scientific accuracy and currency, and remarkable clarity have made Chemistry: The Central Science the leading general chemistry text for more than a decade. Trusted, innovative, and calibrated, the text increases conceptual understanding and leads to greater student success in general chemistry by building on the expertise of the dynamic author team of leading researchers and award-winning teachers